The Role of Incentives Used by Teachers on the Achievement of Autistic Students in East Jerusalem Schools from Teachers' Perspective - Issa, Nancy Mohammed Abdelsalam; Abdel-Rabu, Amal Sami Ahmad (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate the role of educational incentives used by teachers in enhancing the academic achievement and social behavior of students with Autism Spectrum Disorder (ASD) in East Jerusalem schools, from the perspective of teachers. The significance of this study stems from the urgent need to develop effective educational strategies that address the specific needs of this group and support their psychological and educational integration within diverse school environments. The study employed a descriptive analytical methodology. The sample consisted of 80 male and female teachers working in the field of special education in schools and kindergartens in East Jerusalem, selected randomly. The participants included teachers from both inclusive and segregated classrooms, and varied in terms of gender, years of experience, and academic qualifications, which enhanced the diversity of perspectives and the credibility of the findings. The results revealed that both material incentives (such as prizes and rewards) and moral incentives (such as verbal praise and symbolic reinforcement) significantly contribute to improving motivation for learning, increasing focus, and reducing negative behaviors among students with ASD. The findings also indicated that the effectiveness of incentives increases when they are tailored to the individual characteristics of each student and applied consistently within a supportive educational environment. The study recommends training teachers on how to systematically design and implement incentive-based strategies that align with the unique nature of autism. It also emphasizes the importance of strengthening cooperation between schools and families to ensure the continuity of motivational support both in the classroom and at home, which positively impacts students' learning and social adaptation.
Keywords: educational incentives; social behavior; moral incentives; material incentives; school inclusion